Peran Dinas Pemberdayaan Perempuan Perlindungan Anak Pengendalian Penduduk Dan Keluarga Berencana (Dp3ap2kb) Dalam Pencegahan Kekerasan Terhadap Anak Di Kota Surakarta - Dewangga, Kresna; Sugiyarti, Sri Riris (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
Child abuse is a serious problem that affects children's physical and psychological development. As Surakarta City faces this problem, the Office of Women's Empowerment, Child Protection, Population Control and Family Planning (DP3AP2KB) is responsible for prevention. This research analyzes the role of DP3AP2KB in preventing violence against children in Surakarta. This research uses descriptive qualitative research methods, data collection techniques in the form of interviews, observation, documentation. Determination of informants using purposive sampling technique . Data were analyzed using the Miles and Hubberman interaction model. The results showed that DP3AP2KB Surakarta City made efforts to prevent violence against children through five indicators by Siagian (2005), stabilizers, innovators, modernizers, pioneers, and implementers. Stabilizers are carried out through socialization of violence prevention in schools, strengthening FAS, socializing the PUSPAGA Task Force, and strengthening the KLA Working Group. As an innovator, DP3AP2KB utilizes social media, such as Instagram, for FAS publications. The role of modernizer is realized with online services, ULAS complaints, training on the Convention on the Rights of the Child, and commemoration of National Children's Day. As a pioneer, DP3AP2KB provides friendly services and maintains the confidentiality of clients of violence. In its implementing role, DP3AP2KB collaborates with APSAI, Children's Forum, Integrated Service Post, and PUSPAGA Task Force. Although the program is working well, parental and community factors are still influential, so there is a need to develop community programs and training to increase awareness and prevention of violence against children. Keywords: Government Role, Abuse, Children, Child Protection